NATIVE AMERICAN PERSPECTIVE IN LINDA HOGAN’S MEAN SPIRIT - Sathiya, M.; Ramya, S. (International Journal of Research -GRANTHAALAYAH, 2016)
This Paper focuses on the Native American’s struggles and problems through their color and racial discrimination. Linda hogan, a native American and Ecofeminism, a renowned writer. Her novels fully based on the problems of Native Americans, particularly “Mean Spirit” she discussed in an elaborate way and Women also combined together nature and themselves with an effective way.